2018
DOI: 10.1007/s10545-018-0153-8
|View full text |Cite
|
Sign up to set email alerts
|

Succinic semialdehyde dehydrogenase deficiency, a disorder of GABA metabolism: an update on pharmacological and enzyme‐replacement therapeutic strategies

Abstract: We present an update to the status of research on succinic semialdehyde dehydrogenase (SSADH) deficiency (SSADHD), a rare disorder of GABA metabolism. This is an unusual disorder featuring the accumulation of both GABA and its neuromodulatory analog, gamma-hydroxybutyric acid (GHB), and recent studies have advanced the potential clinical application of NCS-382, a putative GHB receptor antagonist. Animal studies have provided proof-of-concept that enzyme replacement therapy could represent a long-term therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 45 publications
1
45
0
Order By: Relevance
“…The role(s) of GABA, β‐alanine and 4‐GBA in the ocular toxicity of VGB remain unknown. Conversely, we and others have demonstrated that supraphysiological GABA impacts the mTOR pathway of autophagy, leading to mitochondrial accumulation and enhanced oxidative stress . β‐Alanine, the structural homologue of GABA, has GABAergic and glycinergic roles that are well‐described, but its role in VGB‐mediated toxicity has not been investigated.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The role(s) of GABA, β‐alanine and 4‐GBA in the ocular toxicity of VGB remain unknown. Conversely, we and others have demonstrated that supraphysiological GABA impacts the mTOR pathway of autophagy, leading to mitochondrial accumulation and enhanced oxidative stress . β‐Alanine, the structural homologue of GABA, has GABAergic and glycinergic roles that are well‐described, but its role in VGB‐mediated toxicity has not been investigated.…”
Section: Discussionmentioning
confidence: 90%
“…Conversely, we and others have demonstrated that supraphysiological GABA impacts the mTOR pathway of autophagy, leading to mitochondrial accumulation and enhanced oxidative stress. 10,11,[50][51][52] β-Alanine, the structural homologue of GABA, has GABAergic and glycinergic roles that are well-described, 53 F I G U R E 1 2 Tissue pools of VGB enantiomers as a function of VGB dose. ND, Not Determined -Prefrontal cortex samples from animals treated with the 35 mg/kg/d dose were used for RNA isolation and thus were unavailable for enantiomer analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, higher mRNA levels of GABA receptor genes were detected in the treated mice. Highly intriguingly, the authors demonstrated significantly decreased brain GHB levels in the treated mice, implicating that the peripherally administrated recombinant SSADH enzyme was capable of clearing the brain GHB excess [70]. This is an important indication for a possible ERT-based treatment in SSADH-D patients with recombinant SSADH, especially in terms of the route of administration.…”
Section: Enzyme Replacement Therapy: Special Requirements For Ssadh-dmentioning
confidence: 89%
“…These treatment concepts and previous clinical trials are summarized in the following paragraphs and in Table 2. Since the treatments and clinical trials have recently been excellently addressed by Vogel and colleagues, we here only shortly summarize the trials and the rationale of these treatments [70]. [84,85] Neuroprotective effects Improves survival of aldh5a -/mice [84,85] Neuroprotective effects…”
Section: Current and Past Clinical Trials In Ssadh-dmentioning
confidence: 99%
See 1 more Smart Citation